Dose-dependent decrease of activation in bilateral amygdala and insula by lorazepam during emotion processing - Paulus, Martin P; Feinstein, Justin S; Castillo, Gabriel; Simmons, Alan N; Stein, Murray B (Archives of general psychiatry, 2005)
Functional neuroimaging may elucidate the pathophysiologic features of anxiety disorders and the site of action of anxiolytic drugs. A large body of evidence suggests that the amygdala and associated limbic structures play a critical role in the expression of anxiety and may be treatment targets for anxiolytic drugs. To determine whether lorazepam dose-dependently attenuates blood oxygenation level-dependent functional magnetic resonance imaging (BOLD fMRI) activation in the amygdala and associated limbic structures during an emotion face assessment task. Fifteen healthy volunteers participated in a double-blind, placebo-controlled, randomized dose-response study. Subjects underwent imaging 3 times (at least a week apart) and were given either a single-dose placebo or 0.25 mg or 1.0 mg of lorazepam 1 hour prior to an MRI session. During fMRI, subjects completed an emotion face assessment task, which has been shown to elicit amygdala activation. The BOLD-fMRI activation in amygdala, insula, and medial prefrontal cortex during the emotion face assessment task. Lorazepam significantly attenuated the BOLD-fMRI signal in a dose-dependent manner in bilateral amygdala and insula but not in the medial prefrontal cortex. Lorazepam did not affect the BOLD-fMRI signal in the primary visual cortex. The current finding provides the first neuroimaging evidence of a dose-dependent change induced by an established therapeutic agent in brain regions known to be critical for the mediation of anxiety. This investigation may help to support the use of BOLD-fMRI with pharmacological probes to investigate the neural circuits underlying anxiety and the use of fMRI as a tool in the development of new anxiolytic agents.